2015
DOI: 10.7567/apex.8.085201
|View full text |Cite
|
Sign up to set email alerts
|

Nanoconstriction-based electrodeless dielectrophoresis chip for nanoparticle and protein preconcentration

Abstract: An electrodeless dielectrophoresis (EDEP) microchip is proposed for the concentration of nanoscale particles and proteins in a 150 nm nanoconstriction gap in a microchannel. Notably, the nanoconstriction is fabricated using a simple thermal-oxidation shrinkage process. It is shown that the nanoconstriction enhances the local electric field intensity by a factor of 1 × 103. The strong electric field and field gradient result in concentration enrichment by factors 1 × 104 and 1 × 103 for nanoparticles and protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Cao et al [26] observed a transition from positive to negative DEP, with the cross-over frequency located between 1 and 10 MHz. The DEP results obtained [2,16,18,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] for proteins other than BSA are summarized in Figure 5. Most research groups report positive DEP for frequencies up to 6 MHz (including direct current), and of particular note is the observation that avidin and prostate specific antigen (PSA) exhibit a DEP cross-over frequency at ~10 MHz [27,37].…”
Section: Summary Of Protein Depmentioning
confidence: 99%
See 1 more Smart Citation
“…Cao et al [26] observed a transition from positive to negative DEP, with the cross-over frequency located between 1 and 10 MHz. The DEP results obtained [2,16,18,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] for proteins other than BSA are summarized in Figure 5. Most research groups report positive DEP for frequencies up to 6 MHz (including direct current), and of particular note is the observation that avidin and prostate specific antigen (PSA) exhibit a DEP cross-over frequency at ~10 MHz [27,37].…”
Section: Summary Of Protein Depmentioning
confidence: 99%
“…One reason for this is the high surface-to-volume ratio of the microfluidic system. This is required because microscope-aided observation of protein DEP calls for flat observation chambers with typical heights between 20 and 200 µm, ranging down to 2 µm [24,39] and even 200 nm [33,34]. This relatively large surface area can result in uncertainties concerning conductivity, pH value and solute concentration.…”
Section: Other Experimental Detailsmentioning
confidence: 99%
“…Nevertheless, progress in nanofabrication has allowed the realization of narrow gaps of a few nanometers between the electrodes, which corresponds to higher values of electric field without affecting the applied voltage. 30 This performance enables trapping also at the nanoscale, and manipulation of small proteins and viruses have been already demonstrated, allowing detection of a very low concentration of biological matter, such as DNA, up to 5 fM with voltage V ≤ 20 V. 31,32 However, similar performance corresponds to a short trapping time (only a few milliseconds), 31 allowing only the counting of objects at the nanoscale. Longer trapping events (up to several seconds), which are useful for the detection and analysis of the target objects, require higher applied voltage with a risk of damage for biological matter.…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticles are bulk materials that are three dimensional at the nanometer scale. In recent years, nanoparticles have been widely implemented for nanoscience applications . Thus, effective and efficient nanoparticle manipulation are significant for advancement in these fields.…”
Section: Dielectrophoretic Manipulation Of Nanomaterialsmentioning
confidence: 99%